The Effect of Cooperative Integrated Reading and Composition Learning Models and Student Team Achievement Divisions on Learning Results and Collaboration of Students in Nursing Theory Material - Yosefina Nelista; Pembronia Nona Fembri; Teresia Elvi (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2019)
Introduction: An understanding of nursing theory requires critical thinking skills. Therefore effective learning methods are needed to improve student understanding. One method of learning that can overcome this is the Cooperative Integrated Reading and Composition (CIRC) method and the Student Team Achievement Divisions (STAD) method. The aim was to analyze the effectiveness of CIRC learning models and STAD Method on student learning outcomes and collaboration. Methods: This study used a quasi-experimental method consisting of two experimental groups with the study design was a post-test design with two comparison treatments. The population in this study were all semester two undergraduate students nursing as many as 30 people divided into two groups—the sampling technique conducted by total sampling. We analyzed the data using the Mann Whitney test with α ≤ 0.05. Results: The mean rank of learning outcomes in the CIRC method was 19.43, and the STAD method was 11.57. The p-value was 0.007 (<0.05), which means that there was a significant difference between learning outcomes in the CIRC group and the STAD group. The mean rank value for student collaboration on the CIRC method was 15.50, and the STAD method was 15.50. The p-value was 1,000 (>0.05), which means there was no significant difference between the collaboration in the CIRC group and the STAD group. Conclussions: There were significant differences between learning outcomes in the CIRC group and the STAD Group. However, there was no significant difference between collaboration in both groups.